Tarsila popular - Pedrosa, Adriano 1965-; Oliva, Fernando (MASP, Museu de Arte de São Paulo Assis Chateaubriand, 2019)
This book is dedicated to the work of Tarsila do Amaral (Capivari, São Paulo, 1886 - São Paulo, 1973) and accompanies a major exhibition at the São Paulo Museum of Art (MASP) on this fundamental artist of Brazilian modernism. From a family of farmers in the interior of São Paulo, Tarsila studied in Paris in the 1920s, where she learned with André Lhote (1885-1962) and Fernand Léger (1881-1955) to then devour modern European styles, such as Cubism, and digest them in an anthropophagic way, producing something of their own, singular and hybrid. Much of the criticism of the artist made to date in Brazil has focused on her French affiliations and genealogies, marginalizing popular themes, characters and narratives. However, popular elements and colors run through all of Tarsila's work: landscapes from the countryside or the suburbs, from the farm or from the favela, populated by indigenous or black people, characters from legends and myths, animals and plants, real or fantastic, represented with their country colors: "pure blue, violet pink, bright yellow, singing green", in the words of the artist. This is the most extensive exhibition catalog on Tarsila do Amaral, bringing together 113 of her works, as well as photographs and documents. Organized by the show's curators, Adriano Pedrosa and Fernando Oliva, it includes unpublished texts by Adriano Pedrosa, Amanda Carneiro, Fernando Oliva, Irene V. Small, Mari Rodríguez Binnie, Maria Bernardete Ramos Flores, Maria Castro, Michele Greet, Michele Bete Petry and Renata Bittencourt, in addition to historical texts by Paulo Herkenhoff and Sergio Miceli, and comments on works by Artur Santoro, Carlos Eduardo Riccioppo, Guilherme Giufrida and Matheus de Andrade.